Studies of jet quenching using isolated-photon+jet correlations in PbPb and pp collisions at sNN=2.76TeV - Chatrchyan, S. (2013)
Results from the first study of isolated-photon+jet correlations in relativistic heavy ion collisions are reported. The analysis uses data from PbPb collisions at a centre-of-mass energy of 2.76TeV per nucleon pair corresponding to an integrated luminosity of 150μb-1 recorded by the CMS experiment at the LHC. For events containing an isolated photon with transverse momentum pTγ>60GeV/c and an associated jet with pTJet>30GeV/c, the photon+jet pT imbalance is studied as a function of collision centrality and compared to pp data and pythia calculations at the same collision energy. Using the pTγ of the isolated photon as an estimate of the momentum of the associated parton at production, this measurement allows an unbiased characterisation of the in-medium parton energy loss. For more central PbPb collisions, a significant decrease in the ratio pTJet/pTγ relative to that in the pythia reference is observed. Furthermore, significantly more pTγ>60GeV/c photons in PbPb are observed not to have an associated pTJet>30GeV/c jet, compared to the reference. However, no significant broadening of the photon+jet azimuthal correlation is observed. © 2012 CERN.